Taxonomy of a katydid genus Mecopoda Serville (Orthoptera: Tettigoniidae, Mecopodinae) from East Asia - Liu, Chun-Xiang; Heller, Klaus-Gerhard; Wang, Xue-Song; Yang, Zhen; Wu, Chao; Liu, Fei; Zhang, Tao (Zootaxa, 2020)
The genus Mecopoda Serville includes eight species, which are mostly distributed in the Oriental region and a few areas in the Palearctic and Australian region. Five species have been recorded in China. Here based on the acoustical and morphological data, we provide a review on the genus Mecopoda in China. We divide the genus Mecopoda into three species groups according to their acoustical characteristics. Six new species and one new subspecies are discovered to be new to science, that it is, M. crescendo sp. nov., M. himalaya sp. nov., M. tibetensis sp. nov., M. confracta sp. nov., M. synconfracta sp. nov., M. minor sp. nov., and M. m. yunnana subsp. nov.. The male of M. marmorata He is also firstly reported with necessary description. Now the number of the genus Mecopoda is 11 in China and 14 in the world. Necessary description and pictures map are presented.